2011
DOI: 10.1186/1756-0500-4-366
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Muslim religious leaders and their attitudes on herbal medicine in Bangladesh: a cross-sectional study

Abstract: BackgroundHerbal Medicines (HMs) are playing major roles in the health of the millions of people worldwide. Muslim Religious Leader (MRLs), being an important component of the society with huge influence on it, could contribute a lot to promote HM. This study was aimed at evaluating perceptions of the MRLs, their satisfaction and attitudes towards HM in Bangladesh.MethodsThis cross-sectional study collected data from a purposive sample of 503 MRLs using an interviewer-administered structured questionnaire duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…This might be due to the perception of low cost and less side effects of that system (Shaheen et al, 2010). They also showed almost similar interest like urban people on herbal medicine which is playing a major role in the health of the millions of people globally (Harun-Or-Rashid et al, 2011). Study also reports that rural people showed their preference more on a religious non-scientific method of treatment called spiritual healing than homeopathy and ayurvedic/unani treatment (Harun-Or-Rashid et al, 2011).…”
Section: General Belief Of Respondents On Various Traditional Systemsmentioning
confidence: 95%
“…This might be due to the perception of low cost and less side effects of that system (Shaheen et al, 2010). They also showed almost similar interest like urban people on herbal medicine which is playing a major role in the health of the millions of people globally (Harun-Or-Rashid et al, 2011). Study also reports that rural people showed their preference more on a religious non-scientific method of treatment called spiritual healing than homeopathy and ayurvedic/unani treatment (Harun-Or-Rashid et al, 2011).…”
Section: General Belief Of Respondents On Various Traditional Systemsmentioning
confidence: 95%
“…Broadly speaking, four types of CAM are being primarily practised in Bangladesh namely herbal, homeopathy, religious and magical methods. Both registered and unregistered (locally known as kabiraj) herbal practitioners are practicing CAM in the country at present [5]. The herbal method of complementary and alternative medicine mainly consists of ayurvedic and unani systems in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Again 37% of them used to visit practitioner, whereas 31% was initially self-medicated. They used TCAM for simple complications like fever (1.9% of respondents surveyed), cough and cold (7.1%), high blood pressure (2.5%), stomach pain (3.4%) and dysentery (1.6%) [5, 7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reported that the lack of training and scientific evidence are the greatest barriers to the clinical use of HM. Therefore, curricula should be designed in order to overcome these barriers [29,30].…”
Section: Participating Subjects and The Administration Of The Questiomentioning
confidence: 99%